Proposal for Improving the monetary loss due to a problem in Quality Management in The Company NEPT COMPUTER S.R.L. Trujillo, 2023 (LACCEI, 2024)
The purpose of this research is to present a Proposal for Improvement in Monetary Loss due to a Problem in Quality Management in the company NEPT COMPUTER S.R.L Trujillo, 2023. Where an exploratory and descriptive study was carried out, and the application of QFD-Casita of Quality, AMFE Matrix, Six-Sigma for each root cause that arose in the company, and thus increase its profitability with its resources. The objective is to analyze the proposal for improvement in the monetary loss due to a problem in quality management in the company NEPT COMPUTER S.R.L. The proposed hypothesis is the determination of the proposal for improvement in the monetary loss due to a problem in quality management in the company NEPT COMPUTER S.R.L. Its dependent variable is the monetary loss and its independent is the proposal for improvement in quality management. Likewise, the investigation used the Ishikawa Diagram to find its 5 root causes such as a lack of maintenance in its equipment, poor sales planning, absences in the guarantee module, inadequate distribution in the warehouse and its inefficient training of personnel. In the Pareto Diagram, two out of five root causes are found due to inefficient staff training with 50.97% and poor stock rotation with 47.32%, and this due to a poor orientation to the business approach, however, it is gave a solution thanks to the improvement proposal. In results we have obtained a benefit of S/ 121,305.00, therefore, it is concluded that an implementation of improvement proposals with quality tools in the company NEPT COMPUTER S.R.L reduces its costs and thus contributes to a good use of it.